2013
DOI: 10.1124/jpet.113.203604
|View full text |Cite
|
Sign up to set email alerts
|

HAMI 3379, a CysLT2 Receptor Antagonist, Attenuates Ischemia-Like Neuronal Injury by Inhibiting Microglial Activation

Abstract: The cysteinyl leukotrienes (CysLTs) are inflammatory mediators closely associated with neuronal injury after brain ischemia through the activation of their receptors, CysLT1R and CysLT2R. Here we investigated the involvement of both receptors in oxygen-glucose deprivation/recovery (OGD/R)-induced ischemic neuronal injury and the effect of the novel CysLT2R antagonistin comparison with the CysLT1R antagonist montelukast. In primary neurons, neither the nonselective agonist leukotriene D4 (LTD4) nor the CysLT2R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 67 publications
1
39
0
2
Order By: Relevance
“…The CysLT 2 R-selective LTMs have only recently become available, but their usefulness in elucidating the role of CysLT 2 R in multiple cellular processes including vascular permeability and ischemic injury is already well established (Ni et al, 2011;Zhang et al, 2013). HAMI 3379 is reported to be 10,000-fold more selective and BayCysLT 2 500-fold more selective for CysLT 2 R than CysLT 1 R (Wunder et al, 2010;Ni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The CysLT 2 R-selective LTMs have only recently become available, but their usefulness in elucidating the role of CysLT 2 R in multiple cellular processes including vascular permeability and ischemic injury is already well established (Ni et al, 2011;Zhang et al, 2013). HAMI 3379 is reported to be 10,000-fold more selective and BayCysLT 2 500-fold more selective for CysLT 2 R than CysLT 1 R (Wunder et al, 2010;Ni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Data indicate that in microglia, both CysLTs and CysLTRs participate in the inflammatory response [45, 46]; nevertheless, the impact of CysLTR-1 and CysLTR-2 in the process is controversial. A number of in vitro evidence indicate a relevant role of CysLTR-1 in microglial activation.…”
Section: Cerebral Localization Of Cyslt Receptorsmentioning
confidence: 99%
“…On the other hand, another study showed that, in primarily cultured microglia, the CysLTR-2 resulted the main regulator of microglia activation. Indeed, the CysLTR-2 antagonist HAMI 3379 inhibited phagocytosis and cytokine release induced by oxygen-glucose deprivation/reperfusion (OGD/R) and by LTD4, whereas montelukast was effective only against OGD/R [46]. …”
Section: Cerebral Localization Of Cyslt Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the responses mediated by CysLT 2 R and CysLT 1 R may vary in different experiments. We recently reported that CysLT 2 R plays a major regulatory role in the activation of rat primary microglia (phagocytosis and cytokine release), whereas CysLT 1 R only regulates cytokine release from microglia [31] . These findings reflect differences between species (rat and mouse) and cell types (primary microglia and BV2 cells [18] ); therefore, the roles of CysLT 2 R in BV2 cell activation should be further clarified.…”
Section: Wwwchinapharcom Yu Sy Et Almentioning
confidence: 99%